The right to identity: Implications of using subjectively-assigned race in US healthcare - Richard S. Witzig (Social Medicine Publication Group, 2014)
In the US, so-called race descriptors have historically been used to ensure control over enslaved and immigrant groups and classes. This paper examines historical, clinical, statistical, and human rights implications for subjectively-assigned race in US healthcare. When compared to other patient descriptors such as age and sex, race is far inferior in terms of method of acquisition, accuracy, precision, and clinical importance. Examination of current US government documents soliciting race reveals categories inconsistent with existing federal guidelines, thereby confounding data at the origin of collection. Subjective and inaccurate labeling can endanger patients who are subjected to race-based disease diagnoses and/or treatments when a more complete ancestry is not elucidated. As an aggregated collection of ethnic groups, racial categories are intrinsically open to statistical confusion, and complete ancestral data should be collected for analysis. The inaccuracies inherent in racial categories can result in study design bias, decreased data quality, and possible corrupted conclusions. The subjective assigning of a person's race - "race-labeling" or "medical race-profiling" - is properly a human rights issue, as the right to accurately define one's individual or group ancestral heritage is a fundamental right supported by the United Nations Universal Declaration of Human Rights.